Solubility and stability of liebigite, Ca2UO2(CO3)3·10H2O(cr), in dilute to concentrated NaCl and NaClO4 solutions at T = 22–80 °C. (December 2019) - Lee, J.-Y.; Amayri, S.; Montoya, V.; Fellhauer, D.; Gaona, X.; Altmaier, M.
Abstract: The solubility and thermodynamic stability of a synthetic liebigite was investigated in NaCl and NaClO4 solutions within a wide range of ionic strength (0.03 m ≤ I m ≤ 5.61 m), pH (7 ≤ pHm ≤ 9, with pHm = –log [H + ]) and temperature (22 °C ≤ T ≤ 80 °C) conditions. A comprehensive characterization of the synthetic solid phase using XRD, quantitative chemical analysis, TG–DTA, SEM–EDS, IR and Raman spectroscopy confirmed the stoichiometry of Ca2 UO2 (CO3 )3 ·10H2 O(cr). At room temperature, liebigite remains stable and controls the solubility of U(VI) in the investigated NaCl and NaClO4 systems with I m ≤ 0.51 m. For the same temperature but high ionic strength (5.61 m NaCl), liebigite transforms into andersonite (Na2 CaUO2 (CO3 )3 ·6H2 O(cr)). This solid phase transformation results in a decrease in solubility of approximately 2 log10 -units at pHm ≈ 8. Solubility data in combination with solid phase characterization (XRD, quantitative chemical analysis) likewise confirm the transformation of liebigite into CaU2 O7 ⋅ x H2 O(cr), Na2 U2 O7 ⋅ x H2 O(cr) and/or other sub-stoichiometric Na-uranate compounds in all systems investigated at T = 80 °C. On the basis of solubility data at room temperature determined in this work, in combination with thermodynamic and activity models available in the literature for the aqueous speciation in the system Ca–U(VI)–carbonate, solubility products for liebigite and andersonite are derived:Ca2 UO2 (CO3 )3 ·10H2 O(cr) ⇔ 2 Ca 2+ + UO2 2+ + 3 CO3 2– + 10 H2 O(l) log K °s, 0 = –(32.3 ± 0.3) Na2 CaUO2 (CO3 )3 ·6H2 O(cr) ⇔ Ca 2+ + 2 Na + + UO2 2+ + 3 CO3 2– + 6 H2 O(l) log K °s, 0 = –(31.8 ± 0.5) These results complement previously reported thermodynamic data, now allowing complete thermodynamic and geochemical calculations for the system UO2 2+ –Ca 2+ –Na + –H + –CO2 (g)–HCO3 – –CO3 2– –H2 O(l), including U(VI) aqueous species and solid compounds, in the context of environmental uranium chemistry and nuclear waste disposal. Highlights: Solubility of liebigite investigated at different temperatures and ionic strengths. Transformation into andersonite observed at T = 22 °C and [NaCl] = 5.61 m. Destabilization of liebigite and formation of uranate phases observed at T = 80 °C. Solubility constants for liebigite and andersonite determined at T = 22 °C. New thermodynamic data used in U phase diagrams for relevant environmental conditions.